Consumer Protection in the Distribution of Natural Medicines Containing Chemical Substances in E-Commerce: An Analysis Based on Law Number 8 of 1999 in Relation to Zudaifu Ointment - Naifa Salma Ufaira; Duhita Driyah Suprapti (Law Research Review Quarterly, 2026)
Advances in digital technology and the growth of e-commerce have broadened public access to various health products, including natural medicines. However, this development has also given rise to the distribution of products that do not meet established safety standards. This issue is evidenced by the circulation of natural medicines such as Zudaifu ointment, which is distributed without marketing authorization and contains pharmaceutical chemical substances. This discrepancy between product claims and actual composition poses health risks and indicates non-compliance with consumer protection regulations. This study aims to analyze the forms of legal protection for consumers and the liability of business actors in the circulation of such products through e-commerce, based on Law Number 8 of 1999 on Consumer Protection. This research employs a normative juridical method using statutory and conceptual approaches, with qualitative analysis through legal interpretation. The findings demonstrate that such distribution constitutes a violation of consumer protection laws, particularly concerning the statutory obligation of business actors to ensure product quality and the accuracy of product information. Sellers, as business actors, bear primary liability and are required to provide compensation for consumer losses if proven at fault. In addition, e-commerce platforms, as electronic system providers, bear indirect responsibility for supervising products within their systems. Accordingly, despite the existing regulatory framework, consumer protection in e-commerce remains constrained by gaps between statutory provisions and their enforcement. Therefore, strengthening supervisory mechanisms, ensuring compliance by business actors, and enhancing the role of digital platforms are necessary to safeguard consumer rights in the digital era.